Tingkat Kreatifitas Belajar Mahasiswa Bimbingan dan Konselinf di Masa Pandemi Covid-19 - Rini Hayati (CERED Indonesia, 2020)
The Covid-19 pandemic have changed all the structures of human life, without exception for the education. Changes that occur both in the learning system and in the learning process, initially through direct contact between lecturers and students. During the Covid-19 pandemic, the learning process was carried out via the internet network or called online. This change requires students to be creative in learning. Student creativity must be owned by both male and female students to be able to understand the material presented online in order to develop their potential. For this reason, creativity in learning during the Covid-19 pandemic is very necessary for all students. This study aims to: describe the learning creativity of male students and the learning creativity of female students. This research method used quantitative descriptive with a sample population of 76 students of guidance and counseling UMN Al Washliyah. The data collection used a closed questionnaire with a Likert scale model with descriptive analysis. The findings of this study are the average score of male student learning creativity of 78.10 with a total percentage of 71%, in the high category, and the average score of female student learning creativity of 81.86 with a total percentage of 74.42%. They are in the high category.